Analisis Respon Tekanan Air Pori Terhadap Muka Air Waduk Pada Bendungan Jatibarang - Angga Setyadi; Suharyanto Suharyanto; Sutarto Edhisono (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The construction of dams is very important for fulfill water demand and as flood control. In addition to having many benefits, a dam also has a high risk. The stability of the dam is strongly influenced by the magnitude of the pore water pressure. The purpose of the study was to determine the response of pore water pressure to the reservoir water level, as well as to find out the comparison of the results of pore water pressure analysis using plaxis 2D and piezometer instrument readings. The piezometer readings are graphed as a function of the reservoir water level. Based on the graph, it can be seen that the piezometer readings correspond to the fluctuations in the reservoir water level. The piezometer upstream side have a faster response to the reservoir water level, which is between 14 to 41 days. While downstream piezometers have a longer response, which is between 25 to 61 days. Pore ​​water pressure analysis using plaxis 2D at location P.17 (upstream) resulted in a smaller value than piezometer reading. While at location P.18 (downstream) it produces a greater value than the piezometer reading. The relative error value of the two analyses is 7.73% < 12% is still considered good, so the difference is acceptable.